Association between Vitamin D and Malondialdehyde in Premenopausal Women & Postmenopausal Women - Kedar Prasad Yadav; Jyoti Batra; Uday Narayan Singh; Rubi Yadav (Asian Journal of Medical Research, 2019)
Background: In the menopausal women, the osteoporosis is characterized by low bone mass leading to enhanced bone fragility and consequent increase in bone fracture risk. These risks are due to calcium & vitamin D deficiency, which occur due to less amount of estrogen production during menopausal age. Aim: To find out the association between vitamin D and Malondialdehyde in Menopausal women. Subjects and Methods: Serum vitamin D and Malondialdehyde levels were measured in 155 postmenopausal women (46-60 years) by using standard methods. They have been compared with 155 premenopausal women (30-45 years) by using student t-test. Results: Serum vitamin D was significantly decreased in postmenopausal women (p<0.0001) as compared to premenopausal women; whereas the serum malondialdehyde level was found to be significantly increased in postmenopausal women (p<0.0001) as compared with premenopausal women. Conclusion: The present study findings indicate decreased levels of serum vitamin D and increased the level of serum malondialdehyde in postmenopausal women. These changes can be used as a good marker for identifying bone related disorders in postmenopausal women. Intimation with supplementation at an early stage may further prevent bone disorder in the later stage of menopause.